Perlindungan Hukum Terhadap Penyewa Dalam Perjanjian Sewa Menyewa Tanah dan Bangunan Rumah Toko Yang Objek Sewanya Telah di Lelang (Studi Kasus Putusan Nomor 70/Pdt.G/2024/PN.JAMBI) - Mutia Adlian; Dwi Suryahartati; Firya Oktaviarni (PT. Hasba Edukasi Mandiri, 2025)
This study examines legal protection for tenants in lease agreements of land and shop buildings whose leased objects were auctioned based on Court Decision Number 70/Pdt.G/2024/PN.Jambi. The research focuses on how tenants’ rights are protected when the leased property is auctioned and the legal consequences of mortgage execution for tenants. Using a normative juridical method with statutory, case law, and conceptual approaches, the findings reveal that although ownership of the leased object changes through auction, the lease agreement remains valid until its expiration. Tenants acting in good faith retain the right to use the property according to the lease terms. The court’s decision thus affirms substantive legal protection and ensures legal certainty for tenants amidst ownership disputes. The study concludes by recommending clearer regulations and legal mechanisms to safeguard tenants’ rights during mortgage executions and calls for greater legal awareness among creditors and business actors to prevent future conflicts.